364 Smoking cessation and lung cancer mortality in a historical cohort of workers with silicosis in Hong Kong, 1981–2006. (11th October 2013) - Tse,; Leung,; Qiu,; Yu,
Abstract : Objectives: To evaluate the impact of smoking cessation on the risk of lung cancer mortality among workers with silicosis. Methods: We recruited all 3202 incident cases of silicosis in Hong Kong from 1981 to 2005 and followed up them till 2006 to ascertain the causes of death. The follow-up rate was 97.5%. We collected each worker's socio-demographics, lifetime smoking habits, lifetime occupational history, and medical history at the initial assessment of diagnosis. We obtained the most recent information on smoking status from medical record. Multiple Cox's regression analysis was performed to examine the impact of smoking cessation. Results: A total of 1562 deaths (48.8%) occurred and 157 of them were from lung cancer. Lung cancer mortality was strongly associated with smoking [former smoking: hazard ratio (HR) = 3.41, 95% CI: 1.23 - 9.46; current smoking: HR = 5.80, 95% CI: 2.13 - 15.74], and a significantly positive gradient was indicated with smoking pack-year and the years of smoking. Lung cancer mortality tended to decreasing at the 10 th year of cessation (HR = 0.64, 95% CI: 0.40 - 1.04) and a substantial decrease was observed after the abstinence of smoking for 20 or more years (HR = 0.22, 95% CI: 0.11 - 0.44). Relative to never smokers, the hazard ratio for lung cancer mortality for silicotics who had never quit smoking was 7.09 (95% CI: 2.57 - 19.59) and it became 4.75 (95% CI: 1.71 - 13.16) for the new quitters who changed their behaviour during the follow-up period, whist a relatively lower risk (HR = 3.47, 95% CI: 1.25 - 9.61) was found among the persistent quitters. Conclusions: Lung cancer mortality decreased substantially with smoking cessation in workers with silicosis, particularly for those who persistently quit smoking for a longer period. Acknowledgement: Pneumoconiosis Compensation Fund Board, Hong Kong